Introduction to Cryptography with Open-Source Software. - McAndrew, Alasdair (Discrete mathematics and its applications., 2012)
Introduction to CryptographyHiding information: confidentiality Some basic definitions Attacks on a cryptosystem Some cryptographic problems Cryptographic protocols Some simple ciphers Cryptography and computer security Basic Number Theory Introduction Some basic definitions Some number theoretic calculations Primality testing Classical Cryptosystems Introduction The Caesar cipher Translation ciphersTransposition ciphers The Vigenère cipher The one-time pad Permutation ciphers Matrix ciphers Introduction to Information TheoryEntropy and uncertainty Perfect secrecy Estimating the entropy of Eng.